Ar-Rahman Method in Improving Al-Quran Reading Skills: Metode Ar-Rahman dalam Meningkatkan Kemampuan Membaca Al-Quran - Camelia, Nabilah; Fauji, Imam (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The ability to read the Al-Quran correctly is a fundamental aspect of Islamic education, especially in Islamic boarding schools that integrate classical and modern approaches. Specific Background: Conventional learning methods often fail to address students’ varied abilities, creating a need for alternative strategies that support both accuracy and fluency. Knowledge Gap: Despite the growing number of Quranic learning methods, limited studies have examined the implementation of the Ar-Rahman method within semi-modern Islamic boarding schools. Aim: This study aims to describe and analyze the implementation of the Ar-Rahman method in improving students’ ability to read the Al-Quran. Results: The findings reveal that the method improves students’ mastery of makhraj, tajwid, and fluency through systematic and structured stages supported by teacher guidance. Novelty: The study provides empirical evidence of how the Ar-Rahman method bridges traditional Quranic pedagogy and modern educational settings. Implications: The results highlight the importance of adopting structured methods like Ar-Rahman to enhance Quranic literacy and contribute to the development of integrated Islamic education systems. Highlights : The Ar-Rahman method supports tajwid and makhraj mastery Structured stages improve students’ fluency in Quranic reading Applicable in semi-modern Islamic boarding school settings Keywords: Ar-Rahman Method, Quran Reading Skills, Tajwid, Islamic Boarding School, Pedagogy